(untitled) (REMUNOM, 2026)
The Lean Six Sigma (LSS) methodology integrates the approaches of Lean Manufacturing (Lean Manufacturing) and Six Sigma (Six Sigma) with the purpose of increasing operational efficiency, reducing costs and providing an alignment between the quality produced and requested by the customer, with focus on reducing waste, process/product variability and increasing value delivery. It has been used by several companies since the 90s, being referred to as a successful methodology in increasing the performance of organizations. Since LSS is a methodology referred to as strategic, the question arises: how have LSS applications evolved in the Brazilian context, based on Case Studies published in the annals of ENEGEP, and what are their main results? With the intention of answering this multidimensional question, the objective of this article was to identify and analyze Case Studies that employ the Lean Six Sigma methodology, using as a source the works published in the proceedings of the National Meeting of Production Engineering (ENEGEP), between the years from 1996 to 2023. For this investigation, a Bibliographic Review was used, with the definition of keywords, article selection filters and categorization of results. As a result, it was possible to identify 16 papers published at ENEGEP and extract information such as objectives, application sectors, supporting tools, and study outcomes.